Informal and Illegal Movement in the Upper Greater Mekong Subregion : Costs and Benefits of Informal Networks for Goods and People - Lynn Thiesmeyer (Institut de recherche sur l$1 (BAsie du Sud-Est contemporaines, 2010)
Myanmar, the second biggest country in terms of area in mainland South East Asia, borders five neighboring countries: China, Thailand, India, Bangladesh, and Lao PDR. Myanmar's longest borders are with China (approximately 1,357 miles) and Thailand (approximately 1,314 miles), and it shares coastal waters with Malaysia and Singapore. Informal activities and informal moment of goods and people have been quite significant due to many factors. Although various policy measures have been developed to mitigate these informal activities, there has not been any study regarding the sources of these informal activities, their costs and benefits, impacts and consequences of the existence and non-existence of these activities, or how these activities could be mitigated without having significant negative economic and social impacts on the local people and the economy as the whole. This paper attempts to identify factors behind causes and effects of informal flows in goods and persons across the borders between Myanmar and its neighboring countries, especially China and Thailand, and to address related issues and possible policy implications. This paper is a result of various surveys and studies in many places in Myanmar, Lao PDR, Thailand, and China from 2005 to 2009 under several research projects.
English
Keywords: goodsnetworks; golden triangle; borders; Upper Greater Mekong Subregion; smuggling; informal trade; economy; underground economy; Vietnam; parallel economy; trafic; trafficking